Wave effect and shyness phenomenon in homogeneous forests of Alnus acuminata - Aguilar-Luna, Jesús Mao Estanislao; Cabrera-Barbecho, Noé; Barrios-Díaz, Benjamín; Loeza-Corte, Juan Manuel (Instituto de Ecología, A.C., 2020)
Wave effect and the shyness phenomenon in Alnus acuminata (Kunth) are canopy parameters rarely studied, but they are important in wood quality for standing trees, therefore, a morphometric modeling of crowns for A. acuminata was carried out in homogeneous forests in the Northern Sierra of Puebla. In 20 rectangular areas of 1000 m2, it was evaluated: total height (TH), diameter at breast height (DBH), crown diameter (CD) and canopy coverage (CC). To the data that did not meet the normality assumption, the Kruskal Wallis test was applied; for those who did, the analysis of variance (ANOVA) was used, with tests of mean comparison by Tukey (α ≤ 0.05). The forest value index was 14.99, whereby its two-dimensional structure is normal, based on the DBH, TH and CC. The average slenderness index was 93.52, making the trees not stable to mechanical damage. The vital space index was 38.92, which is high and shows a better development of the trees with low intraspecific competition. At the canopy level, we observed a pattern that follows a rising wave effect, oscillatory and constant in groups of 10 trees. The shyness phenomenon showed an average crack opening of 27.39 cm between crowns whereby this phenomenon is well-defined for the species. It is concluded that in the cups of A. acuminata, the wave effect occurs because of the inequality in the acquisition of resources, and one way to minimize this inequality is through the phenomenon of botanical shyness.